Nutrition Co-Benefits of Climate-Smart Agriculture in Myanmar - International Institute of Rural Reconstruction; CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
This primer is generated from CCAFS’ and IIRR’s work in Myanmar. Advocates and proponents of climate-smart agriculture are provided with unique opportunities to leverage the nutritional benefits of agriculture. Working with, and building on, local and existing farming systems is a logical pathway which can better ensure that CSA interventions are sustained while also contributing to food and nutrition security.